2015
DOI: 10.1371/journal.pgen.1005248
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Changes of Gene Expression and Function Reveal Genomic and Phenotypic Complexity in SLE-like Disease

Abstract: The complexity of clinical manifestations commonly observed in autoimmune disorders poses a major challenge to genetic studies of such diseases. Systemic lupus erythematosus (SLE) affects humans as well as other mammals, and is characterized by the presence of antinuclear antibodies (ANA) in patients’ sera and multiple disparate clinical features. Here we present evidence that particular sub-phenotypes of canine SLE-related disease, based on homogenous (ANAH) and speckled ANA (ANAS) staining pattern, and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…To screen for functional relationships among the vitiligo candidate genes, we carried out pathway analysis of the protein products of all positional candidate genes at all 48 confirmed loci and the seven suggestive loci using g:PROFILER 10 , PANTHER 11 , and STRING 12 . To assess enrichment of association signals in different functional genomic categories contributing to vitiligo heritability, we applied stratified LD score regression 51 to the combined CMH GWAS123 summary statistics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To screen for functional relationships among the vitiligo candidate genes, we carried out pathway analysis of the protein products of all positional candidate genes at all 48 confirmed loci and the seven suggestive loci using g:PROFILER 10 , PANTHER 11 , and STRING 12 . To assess enrichment of association signals in different functional genomic categories contributing to vitiligo heritability, we applied stratified LD score regression 51 to the combined CMH GWAS123 summary statistics.…”
Section: Methodsmentioning
confidence: 99%
“…Considering proteins encoded at the 23 newly confirmed vitiligo candidate loci, at least twelve (CTLA4, TICAM1, PTPRC, FARP2, UBE2E2, NRROS, CPVL, ARID5B, PTPN1, TNFSF11, TNFRSF11A, IRF3, and perhaps also IL1RAPL1) play roles in immune regulation, and PPP3CA may regulate FOXP3 via NFATC2 and is associated with canine lupus 12 . Six (FASLG, BCL2L11, BCL2L12, SERPINB9, NEK6, BAD) are regulators of apoptosis, particularly involving immune cells.…”
mentioning
confidence: 99%
“…were enhanced, PPP3CA gene acts in the downstream of BCR via MAPK signaling pathway, was also had a higher expression in CaN®NEAF, KEGG module in SLE patients. Similarly, the strong association of PPP3CA with SLE-like disease has been described as newly [57]. The transcription factor AP-1…”
Section: Discussionmentioning
confidence: 93%
“…These results suggested that the highly co-expressed genes in the same module have potential biological significance [ 6 ]. Each module might represent specific clinical features of RC patients [ 3 , 22 ].…”
Section: Resultsmentioning
confidence: 99%